The Corsair Affair and articles relating to the writings - Hong, Howard V. (Howard Vincent), 1912-2010; Hong, Edna H. (Edna Hatlestad), 1913-2007; Kierkegaard, Søren, 1813-1855; Møller, P. L. (Peder Ludvig), 1814-1865; Goldschmidt, Meïr, 1819-1887 (Kierkegaard's Writings., 2009)
The Corsair affair has been called the ""most renowned controversy in Danish literary history."" At the center is Søren Kierkegaard, whose pseudonymous Stages on Life's Way occasioned a frivolous and dishonorable review by Peder Ludvig Møller. Møller was associated with The Corsair, a publication notorious for gossip and caricature. The editor was Meïr Goldschmidt, an acquaintance of Kierkegaard's and an admirer of his early work. Kierkegaard struck back at not only Møller and Goldschmidt but at the paper as a whole. The present volume contains all of the documents relevant to this dispute, p.